METODE PENILAIAN AKHLAK (STUDI KASUS DI SMPIT AT-TAUFIQ BOGOR) - Bamualim, Ahmad bin Umar (Tawazun: Jurnal Pendidikan Islam, 2018)
The aim of this research is to know the concept of student’s akhlak and its relevance to national education. The urgency of this research is to improve the quality of education to form characterized and civilized human who increasingly chaotic. The research method use the Qur’an and Sunnah, literature study (library research), and other relevant sources. The result of the research shows the relevance of his moral valuation method with assessment method in SMPIT AT-TAUFIQ Bogor specifically and national education generally. The Qur’an, Sunnah, and guidance of the salaf strengthen the building of moral judgments that I have embraced